Effect of neuromotor exercises on balance in basketball players: a systematic review with meta-analysis (Research, Society and Development, 2022)
Aim: the purpose of this review is to evaluate the effect of lower limb neuromotor exercises on static and dynamic balance in basketball players. Methods: the search strategy was carried out in the following databases: Medline/Pubmed, LILACS, Scopus, and PEDRO. Certainty of evidence was assessed by GRADE for posteromedial, posterolateral, and anterior directions, and composite score of the Star Excursion Balance Test. Results: the initial search identified 520 studies. Of them, six studies were included in this review, and three of them were included in the meta-analysis (n = 64). GRADE evaluation indicated low level of certainty of evidence for posteromedial (MD = 4.92%; 95% CI = -1.44 to 11.29; P = 0.13; I2 = 55%), posterolateral (MD = 6.08%; 95% CI = 2.76 to 9.40; P = 0.0003; I2 = 19%) and anterior (MD = 4.87%; 95% CI: 2.84 to 6.89; p